O programa residência pedagógica e suas contribuições para a formação docente em Abaetetuba-PA - RODRIGUES, Iêda ribeiro (2019)
One of the major concerns in the context of education, especially in the municipality of Abaetetuba-Pa, is related to teacher training for basic education. It is of the utmost importance that public programs and policies aimed at teacher education are monitored and evaluated, in order to achieve significant results regarding the proposed objectives. The Pedagogical Residency Program is an action implemented by Capes to meet the objectives of the National Policy for Teacher Education of the Ministry of Education. From the need to systematize the evaluation of residents about the program to have the perception that the student is favored after living their future reality while preparing for the profession, the objective is to present the results that the Pedagogical Residency Program provided for the academic formation of the students of the Abaetetuba-Pa field education course. It is based on the historical process of the program, emphasizing the Rural Education subproject. Within a qualitative approach, questionnaires were applied by email to residents and preceptors of the subproject. Coming to the results related to the contributions of the program actions to the residents, the teacher training and the field school. Where the approach of the schools with the IES presented gratifying results, for the formation of the residents in their acting as a teacher.